The Relationship between Lipid Profile and Testosterone in Acne Vulgaris (Journal of the College of Basic Education, 2022)
Acne vulgaris is a multifactorial disease affecting a majority of the adolescent population. The objective of this study was to estimate the lipid profile and hormone testosterone in patients with acne and in control groups, also to test the correlation between lipid profiles levels and testosterone level in acne patients. Prospective study was performed in 60 patients of acne volgaris . Lipid profile and serum testosterone levels were measured. Their results were compared with a group of 30 age-matched healthy groups .Total cholesterol (TC), HDL-C and LDL-C levels were lower in acne patients. Testosterone levels were increased in acne patients. Positive correlation was found between testosterone and TC. In conclusion, acne patients have some abnormality in lipid profile and hormone testosterone. These abnormalities must be considered in the pathologenesis as well as in the treatment of acne patients.